2014
DOI: 10.1155/2014/850810
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Rapid Latex Agglutination in Estimation of von Willebrand Factor: Method Revisited and Potential Clinical Applications

Abstract: Measurement of von Willebrand factor antigen (VWF : Ag) levels is usually performed in a specialised laboratory which limits its application in routine clinical practice. So far, no commercial rapid test kit is available for VWF : Ag estimation. This paper discusses the technical aspect of latex agglutination method which was established to suit the purpose of estimating von Willebrand factor (VWF) levels in the plasma sample. The latex agglutination test can be performed qualitatively and semiquantitatively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Bead-antigen mixtures were allowed to incubate at room temperature for 2 h. After incubation, plates were microscopically (10X magnification) evaluated for determination of agglutination. Agglutination was recorded on an arbitrary scale of 0-4 with 0 as no visual agglutination and 4 as very strong agglutination (Mahat et al, 2014).…”
Section: Agglutination Assaymentioning
confidence: 99%
“…Bead-antigen mixtures were allowed to incubate at room temperature for 2 h. After incubation, plates were microscopically (10X magnification) evaluated for determination of agglutination. Agglutination was recorded on an arbitrary scale of 0-4 with 0 as no visual agglutination and 4 as very strong agglutination (Mahat et al, 2014).…”
Section: Agglutination Assaymentioning
confidence: 99%
“…These results raise the possibility that a semiquantitative assay could be developed by configuring cell density scales or coupling with microscopy observations. Some studies have suggested that the agglutination assay is not suitable when the bacterial cell density is very low (Fronczek, ; Mahat, Abdullah, & Che Hussin, ).…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 antigen-latex particle conjugates were prepared by passive adsorption following the procedures described by Mahat et al 24 , with some modifications. Briefly, 0.4 mL of 5% (w/v) latex suspension was centrifuged at 3,000 g for 5 minutes at room temperature, and the supernatant was discarded.…”
Section: Methodsmentioning
confidence: 99%